Nova metodologia dos rankings Times Higher Education e a pontuação em citações das universidades da América Latina - Cangiani, Maria Laura Machado (2024)
Rankings are ubiquitous in monitoring university performance, but there is controversy about their procedures. One intriguing fact is the divergence observed between the overall position, research position and citation position occupied by the universities evaluated by THE Latin America University Rankings: the universities best evaluated by this ranking are also well evaluated in research, but they are not the best evaluated in citation. This divergence is due to the methodology for scoring universities in the Citation indicator, based on Field-Weighted Citation Impact and which has undergone recent adjustments, including the introduction of the Research Strength metric, aiming to better represent the performance of universities in citation. This research aims to evaluate the new methodology of the Times Higher Education by simulating the calculation of Research Strength. The research is configured as exploratory, quantitative and comparative in that it seeks to expand knowledge about the impact caused by a recently implemented methodology, using position and score data from the rankings, as well as publication and citation data, in addition to its own calculations, comparing the performance of several universities. Data from THE Latin America University Rankings 2022 and the Scival Platform were used. High correlations were found between the Overall, Teaching and Research Scores and low correlation between the Overall and Citation Scores and between Citation Score and Field-Weighted Citation Impact. The simulation carried out among the top 100 universities in THE Latin America University Rankings 2022, using Research Strength, showed that this metric may have the opposite effect to that expected, favoring the best citation performance of universities with many publications with many co-authors.